The lure of Pokemon video games and the savage mind - Nakazawa, Shin'ichi 1950-; Japan library (2019)
From its humble beginnings as a video game launched in the mid-90s, Pokemon has become a global entertainment franchise, even reaching into the world via "augmented reality" with the mobile game Pokemon GO. In the work, Nakazawa Shinichi argues that the Pokemon worldview is the best contemporary example of Claude Le?vi-Strauss's "savage mind" (la pense?e sauvage), suggesting that computer games can often be viewed as attempts to reconnect the human unconscious with the true, hidden essence of nature. --Publisher Space Invaders revolution -- The birth of monsters -- Eros, Thanatos, and RPGs -- The triumphs of Pokemon -- Totemism today -- The Gift and the world of gaming -- Epilogue --Afterword to the first edition (1997) -- Appendices. Pokemon GO, or, the dream of the good walker -- The game freaks who play with bugs -- The origins of Pokemon / by Satoshi Tajiri.
Games are often thought to draw children out of nature and into isolated, closed spaces. In The Lure of Pokemon: Video Games and the Savage Mind, however, Nakazawa Shinichi shows how the Pokemon series of video games, far from standing in opposition to nature, actually seeks to represent the true, hidden essence of the natural world. From humble beginnings as a video game launched in the mid-90s, Pokemon has become a global entertainment franchise, even reaching into the real world with "augmented reality" via the mobile game Pokemon Go. Nakazawa argues that the Poke?mon worldview is the best contemporary example of Le?vi-Strauss's "savage mind" (la pense?e sauvage). As the natural environment is transformed around them, the author suggests, children that would once have directly observed and explored nature encounter it through technology instead. Contemporary games and other narratives can often be viewed as attempts to reconnect the human unconscious with nature, undoing the separation effected by the scientific, rational thought of Western modernity. Nakazawa also shows how games like Pokemon recreate deep-rooted social patterns. When characters capture monsters, carry them around in "Poke? Balls," and swap them with other characters, they are part of a tradition in which trade is more than just the exchange of goods. Barter is a much more profound form of communication in which each participant also receives part of the other. The author supports his argument through close analysis of the history and even prehistory of video games in Japanese culture. Drawing on mythology, Freudian and Lacanian psychoanalysis, and other resources, he explores cultural touchstones like Space Invaders, Ultraman, and the RPG as a genre, showing how their rich, direct expression appeals directly to the urges and impulses within children themselves, helping them come to terms with their place in the world. The Lure of Poke?mon: Video Games and the Savage Mind is both a work of game criticism revealing la pense?e sauvage within today's video games and an examination of Japanese culture as the context from which the Poke?mon phenomenon was born." -- Publisher's description.
Translation of: Pokemon no shinwagaku.
"Originally published in Japanese under the title Poketto no naka no yasei by Iwanami Shoten, Publishers in 1997, and republished in pocket paperback by Shinchosha Publishing Co., Ltd. in 2004 and in another pocket paperback format under the new title Pokemon no shinwa gaku: Shinpan poketto no naka no yasei by Kadokawa Corporation in 2016."--Title page verso.
Includes bibliographical references.
Japanese
Keywords: Video games and Japan; Structuralism -- Children -- Japan; Pokemon (Game); Mack, Ted